Evaluation of Architectural Spatial Quality in Patients' Rooms in the Context of User Satisfaction in General Hospitals: a Case study in Gaziantep - Ergenoglu, Asli Sungur; Tanritanir, Anil (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
Healthcare facilities are being evaluated throughout the world determine to what extent they are meeting the needs of patients. Evidence-based research is gaining importance in Turkey as hospital designers strive to increase patients' satisfaction. In this paper, we will examine the results of a case study conducted to evaluate the spatial quality of patients' rooms in the context of their satisfaction. Two private general healthcare buildings in Gaziantep were examined in the case study. We chose to evaluate private hospitals because we assumed they would have better conditions than state hospitals. We also took into consideration that these healthcare institutions are in the process of accreditation. Surgeries are frequently conducted here and long-term stays are common. In order to evaluate the subject thoroughly, we used a both a questionnaire and a checklist to gather information. Problems with the spatial quality of the rooms will be identified in the discussion chapter. The examples chosen for the study have showed significant development in available services and space. Using the data obtained from the case study, we have chosen three categories of design criteria through which to evaluate these facilities. Findings will be presented under the headings of function, aesthetics and safety in the results chapter.
Keywords: Healthcare buildings; patient room floor; patient room; patient care unit; architectural space quality; patient satisfaction; Architecture